Influence of Drying Methods on the Morphological Features, Microstructural Properties, and Antioxidant Performance of Floccularia luteovirens: A Metabolomic Analysis - Mengjun Xiao; Tao Wang; Chuyu Tang; Min He; Xiaojian Pu; Tingjing Zhao; Yuling Li (Journal of Fungi)
Floccularia luteovirens (F. luteovirens) has garnered increasing attention as an ingredient in both the pharmaceutical and food industries. Depending on the drying method, the accumulation of metabolites can greatly affect the quality. This research employed an untargeted metabolomics (LC-MS/MS) strategy to elucidate the similarities and differences in the morphological characteristics, microstructure, antioxidant capacity, and metabolic profiles of F. luteovirens subjected to three distinct drying methods: natural air-drying (YG), oven-drying (HG), and vacuum freeze-drying (DG). Our findings indicated that the color of F. luteovirens samples dried using the YG and HG methods was yellow-brown, exhibiting a high degree of browning, whereas the samples processed by the DG method displayed a golden-yellow hue and a desirable fullness. Regarding microstructure, the F. luteovirens samples from the YG and HG methods exhibited small and unevenly distributed pores, in contrast to the samples from the DG method, which were structurally intact and characterized by large inter-tissue pores. The antioxidant activity exhibited by F. luteovirens samples, which were processed using the DG method, was found to be significantly superior compared to the antioxidant activity of samples dried using two other methods. A correlation analysis indicated a significant link between antioxidant capacity and lipid as well as lipid-like molecules. Metabolomic analysis identified 1617 metabolites across 15 superclasses, with lipids, lipid-like molecules, organic acids and derivatives, and organic heterocyclic compounds being the predominant metabolites in F. luteovirens. Furthermore, KEGG enrichment analysis highlighted 20 pathways, indicating that the metabolism of amino acids could be significantly involved in the metabolic processes linked to the drying of F. luteovirens. This research clarifies how different drying techniques impact the metabolites or metabolic pathways of F. luteovirens, identifying the mechanisms that influence its quality and providing a reference for optimizing its processing and storage.